The geography and co-location of European technology-specific co-inventorship networks - Julian P. Christ (Universität Hohenheim, 2009)
This paper contributes with empirical findings to European co-inventorship location and geographical coincidence of co-patenting networks. Based on EPO co-patenting information for the reference period 2000-2004, we analyze the spatial configuration of 44 technology-specific co-inventorship networks. European co-inventorship (co-patenting) activity is spatially linked to 1259 European NUTS3 units (EU25+CH+NO) and their NUTS1 regions by inventor location. We extract 7.135.117 EPO co-patenting linkages from our own relational database that makes use of the OECD RegPAT (2009) Files. The matching between International Patent Classification (IPC) subclasses and 44 technology fields is based on the ISI-SPRU-OST-concordance. We confirm the hypothesis that the 44 co-inventorship networks differ in their overall size (nodes, linkages, self-loops) and that they are dominated by similar groupings of regions. The paper offers statistical evidence for the presence of highly localized European co-inventorship networks for all 44 technology fields, as the majority of linkages between NUTS3 units (counties and districts) are within the same NUTS1 regions. Accordingly, our findings helps to understand general presence of positive spatial autocorrelation in regional patent data. Our analysis explicitly accounts for different network centrality measures (betweenness, degree, eigenvector). Spearman rank correlation coefficients for all 44 technology fields confirm that most co-patenting networks co-locate in those regions that are central in several technology-specific co-patenting networks. These findings support the hypothesis that leading European regions are indeed multi-field network nodes and that most research collaboration is taking place in dense co-patenting networks.
urn:nbn:de:bsz:100-opus-4426
Keywords: C8; O31; O33; R12; 330; co-patenting; co-inventorship; networks; linkages; co-location; RegPAT